Effects of different physical education programmes on children's skill- and health-related outcomes: a pilot randomised controlled trial. Issue 15 (3rd August 2017) - Gallotta, Maria Chiara; Emerenziani, Gian Pietro; Iazzoni, Sara; Iasevoli, Luigi; Guidetti, Laura; Baldari, Carlo
ABSTRACT: Aim of this study was to evaluate the effectiveness of two different 5-month physical education (PE) interventions conducted by a specialist PE teacher on primary school children's skill- and health-related outcomes. About 230 children were randomly assigned to one of three intervention groups: experimental_1 group, experimental_2 group or control group (school curriculum given by the generalist teacher). Pre- and post-intervention tests assessed pupils' fitness (pacer, curl-up, push-up, trunk lift, sit and reach tests) and gross motor coordination (shifting platforms, balance beam, jumping laterally, hopping on one leg over an obstacle tests). Both experimental groups significantly improved some fitness and coordinative tests after the intervention period when compared with control group. However, no differential changes on coordinative development were observed between the 2 experimental groups. Results of this study demonstrated that children benefitted from a well-structured PE intervention conducted and supervised by a specialist PE teacher improving their motor skills and fitness.